Validity and reliability of the Oil Palm Fertilizer Infographic Mobile App module to enhance knowledge practices in palm fertilization among smallholders - Ishak, Azura; Murdi, Ahmad Afandi; Hashim, Khairuman; Zawawi, Norliyana Zin; Muhammed, Abdullah; Rahmat, Masura; Shahrani, Shahrina; Abd Rahman, Rohizah; Zainal, Noor Faridatul Ainun (Semarak Ilmu Publishing, 2024)
Implementing best practices in oil palm fertilisation is pivotal for enhancing fresh fruit bunch production within the oil palm cultivation sector. However, small-scale farmers in Malaysia still encounter a notable deficiency in understanding fertiliser management. Therefore, providing easily accessible and comprehensible sources of palm fertilisation information is crucial, with a focus on materials containing verified and dependable content from the Malaysian Palm Oil Board (MPOB). This study aims to evaluate the validity and reliability of the oil palm fertiliser infographic mobile app module for smallholders. The module’s content was made simpler by referring to multiple documentation sources regarding recommended palm fertilisers by the Agronomic Unit of the MPOB. The infographic module is designed to encourage best practices in palm fertilisation for smallholders through a user-friendly mobile app platform. A module draft was submitted to five specialists in palm fertiliser and module development to assess its validity. Several improvements were made based on the comments and feedback gained from these experts. 55 individuals, including smallholders, contributed to evaluating the module’s reliability and the impact of the knowledge practices in palm fertilisation. The entire module’s content attained a validity rate of 90%, confirming the acceptance of its content validity. Furthermore, the module recorded a Cronbach’s alpha value of 0.981, indicating a high level of reliability. The utilisation of this module within the mobile app platform suggests that the application could effectively improve users’ knowledge of palm oil fertilisation practices. These findings demonstrated that the Infographic Oil Palm Fertilizer is appropriate and successful in achieving the intended learning objectives.